Biosynthesis and characterization of silver nanoparticles generated from peels of Solanum tuberosum (potato) and their antibacterial and wastewater treatment potential - Deepa,; Dhanker, Raunak; Kumar, Ram; Kamble, Shashank S.; Kamakshi,; Goyal, Shubham (Frontiers in Nanotechnology, 2023)
Global food production consumes a large fraction of energy budget, land area, and freshwater; however, a larger fraction of the produce is lost or unutilized, which has potential to produce useful products for human use. The biogenic synthesis of silver nanoparticles from such waste food appears to be a promising strategy. A conservative estimate of 70–140 thousand tons of potato peels is produced annually by food-chain companies globally; however, they are primarily utilized to produce substandard feed for livestock or manure. For the formation of highly profitable compounds, enhancement of value, and the process of extraction, such as nanocomposite, organic antioxidants, and organic meal inclusions, potato peels can be used as a cheap, productive, and readily available source of raw material. In the present research, silver nanoparticles (AgNPs) were extracted from the peels of potato (Solanum tuberosum). The fabrication of potato peel-derived AgNPs was established using UV-visible spectroscopy analysis. Approaches like X-ray diffraction (XRD), attenuated total reflection-infrared (ATR-IR) spectroscopy analysis, and field emission scanning electron microscopy (FESEM) were used to determine the characteristics of the AgNPs. Additionally, strains of Gram-positive bacteria such as Staphylococcus aureus (S. aureus) (ATCC 25923) and Gram-negative bacteria such as Escherichia coli (E. coli) (ATCC 25922) were used to determine the antibacterial activity of AgNPs via the disc diffusion technique. The antibacterial properties of AgNPs could help protect food from microbial contamination. Furthermore, AgNPs were tested for their potential application in purification of industrial wastewater. The results revealed that AgNPs derived from the potato peels could be used in industrial and biomedical applications and possess excellent antibacterial activity. Our research suggests that AgNPs can be extracted from a safe and ecofriendly fabrication technique from largely unused potato peels that have a great potential for inhibiting the bacterial growth and for the in situ purification of wastewater in the upcoming years. Therefore, besides value addition to the farm produce, such recycling of potato peels is likely to reduce the burden of the solid waste volumes in agro-centers, kitchen wastes, and food industries across the globe.